Pengaruh manajemen kepala sekolah, profesionalisme guru, dan motivasi berprestasi terhadap efektivitas kerja guru sekolah dasar di Kecamatan Kledung Kabupaten Temanggung - Winardi Suyanto; Samidjo Samidjo (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2016)
This research aims: 1) to find out how much influence the management of the principal, teacher professionalism, and achievement motivation on the work effectiveness of primary school teachers in Subdistrict Kledung, Temanggung Regency. 2) to find out how much influence the principal management, the work efficiency of a primary school teacher in Subdistrict Kledung, Temanggung Regency. 3) to find out how much influence the professionalism of teachers on the work effectiveness of primary school teachers in the Subdistrict Kledung, Temanggung Regency. 4) to find out how much influence the achievement motivation on the work efficiency of the primary school teachers in the Subdistrict Kledung, Temanggung Regency. This research use method a quantitative approach which conducted in the subdistrict Kledung, Temanggung Regency, with a population of a number of 157 teachers in 14 primary schools in the subdistrict Â Kledung, which is then taken a sample of a number of 114 teachers. Techniques a data collection conducted through the submission of a questionnaire which contains statements about the management of the principal, teacher professionalism, achievement motivation and the work effectiveness. The analysis technique used is a technique of descriptive statistics, of multiple regression techniques, the partial correlation coefficient analysis, and assess the goodness of fit by the F test, T-test, and the coefficient of determination. Analysis result showed the variable contribution of principals management, teacher professionalism, and achievement motivation simultaneously influence positive which significant against the variable effectiveness of work teachers. From the analysis and the discussion of can pulled conclusion 1) the principal's management, teacher professionalism, and achievement motivation, simultaneously or partially the influential positive which significant against the effectiveness of the primary school teachers in the subdistrict Kledung, Temanggung Regency. 2) The Principal Management influential positive which significant against the effectiveness of the work, so management which done well will directly affect the work efficiency of the teacher. 3) The professionalism of teachers influential positive significant against the effectiveness of the work, so that teachers are which professionals in their duties will demonstrate the effectiveness of the better so as to provide better working results and quality. 4) Achievement motivation influential positive which significant on the effectiveness of the work, so that teachers who have high achievement motivation will affect the effectiveness of its work.